Mast Cells in Gut and Brain and Their Potential Role as an Emerging Therapeutic Target for Neural Diseases - Traina, Giovanna (Frontiers in Cellular Neuroscience, 2019)
The mast cells (MCs) are the leader cells of inflammation. They are well-known for their involvement on allergic reactions through degranulation and release of vasoactive, inflammatory and nociceptive mediators. Upon encountering potential danger signal, MCs are true sensors of the environment, the first to respond in rapid and selective manner. The MC activates the algic response and modulates the evolution of nociceptive pain, typical of acute inflammation, to neuropathic. Yet, MC may contribute to modulate intensity of the associated depressive and ansiogenic component on the neuronal and microglial biological front. Chronic inflammation is a common mediator of these co-morbidities. In parallel to the removal of the etiological factors of tissue damage, the modulation of MC hyperactivity and the reduction of the release of inflammatory factors may constitute a new frontier of pharmacological intervention aimed at preventing the chronicization of inflammation, the evolution of pain, and also the worsening of the depression and ansiogenic state associated with it. So, identifying specific molecules able to modify MC activity may be an important therapeutic tool. Various preclinical evidences suggest that the intestinal microbiota contributes substantially to mood and behavioural disorders. In humans, conditions of the microbiota have been linked to stress, anxiety, depression, and visceral and centralized pain. MC is likely the crucial neuroimmune connecting between these components. In this review, the involvement of MCs in pain, stress and depression is reviewed. We focus on the MC as target that may be mediating stress and mood disorders via microbiota-gut-brain axis.